Julia Morgan and Emma Morgan with Kappa Alpha Theta sorority sisters, c. 1894 (with identifications) - F. A. Webster (1860-1933)::::::photographer::: (1894)
Copy print of c. 1894 Kappa Alpha Theta sorority portrait with handwritten identification of member names, including Julia Morgan and Emma Morgan. (Back row: Emma Morgan North, Mabel Gray, Anita Simms, Louise Whipple McCray, Mabel Simms, Eugenia Langstrom. Middle row: Ethel Olney Easton, Lucretia Watson, Louise Shepherd Lewis, Frances Boggs, Mary Only Bartlett (Sr.), Mary McLean Olney, Ann Brower. Front row: Grace Sutton, Cecelia Raymond Smith, Eliza Blake Thatcher, Beatrice Fox, Maida Castlehum, Julia Morgan) The photographer is Frederick Arthur Webster, listed at 1069 Broadway in Oakland, California. See an alternate print: https://digital.lib.calpoly.edu/rekl-2067